Recursos hídricos de la microcuenca Pichgacocha y propuesta de guías de prácticas para su protección y conservación - Flores Manrique, Ayar (2017)
The researchaims todetermine theinfluence of thediagnosis ofthe water resources oftheMicrocuencaPichgacochaforthe development and implementationofpractice guidelinesand fieldlaboratory. The methodology includesfieldworkand laboratory work. The population and the sampleis 35 students. Toassess the level ofinfluence that thediagnosisof water resourcesand the application ofpractice guidelinesforlaboratory and fieldevaluationis reached-2-1and evaluationwith the following results: an average11(-1 assessment) averageand15(-2assessment). It alsomanages to developlearning contentconceptual, proceduraland attitudinal.